The Mediating role of Sustainable Supply Chain in the Relationship between ECO-Strategic Orientation and the Reverse Logistic in Thai Electronic Industry - Chayanan Kerdpitak; Tippawan Chakphet; Sumneung Maneechay; Sutas Jaepho (International Journal of Supply Chain Management, 2020)
The current study provides important insight in the relationship between sustainable supply chain, ECO-strategic orientation and the reverse logistic. The SEM-PLS is used to analyses the data collected from the electronic industry of Thailand’s findings of the current research offer alternatives for the managers who are keen to develop sustainable supply chain initiatives. Significance of strategic orientation i.e. eco-innovation and eco-reputation should not be ignored by the firms, if the development of sustainable supply chain   initiatives is intended by the organization’s decision makers, thus, eco-innovation and eco-reputation are found to be the key enablers of sustainable supply chain   initiatives. The obtained results are integrated with the managerial implications. The findings of this study provide empirical validation needed to make investment in sustainable SC initiatives. In addition, a strong evidence is provided about the benefits arising from reverse logistics. The assurance of obtaining benefits from sustainable supply chain provide confidence to the managers. Therefore, ecological requirements are considered as key production and product criteria, specifically for those firms which try to find ways such as staying profitable and maintaining competitiveness to achieve economic sustainability. Therefore, adopting sustainable supply chain   initiatives may result in value creation, provide means for achieving competitive advantage, and reverse logistics.